Distant voices: coming home - participant interviews, 2017-2019 - McNeill, Fergus (UK Data Service, 2022)
This data set comprises transcripts of audio-recorded semi-structured interviews with participants in 2-day or 3-day collaborative songwriting workshops (which we refer to as 'Vox Sessions') which were loosely themed around reintegration after state punishment. The workshops were undertaken in a variety of settings, in prisons and communities, with criminal justice-involved people. Distant Voices responded to pressing public policy and political challenges created by huge rises in the numbers of people subject to penal sanctions and by high levels of reoffending. Turning conventional understandings of 'offender rehabilitation' on their head, the project was concerned not with 'correcting offenders' but rather with exploring and changing how they are received when 'coming home' after punishment. The project aimed: (1) to improve academic and public understandings of social re/integration after punishment; (2) to develop innovative practices to better support re/integration; and (3) to better engage a range of citizens, communities and civil society institutions in re/integration. As a collaborative action research project drawing on criminology, popular music, politics and other disciplines, Distant Voices combined creative practices (principally songwriting and sharing), research and knowledge exchange to enable dialogue and learning about re/integration -- and to practice and support it. Its participatory methods drew together a wide range of differently situated citizens, organisations and associations to form a 'community of enquiry' and of creative practice. This range of participants worked across three inter-related activities. (1) In 'Co-creative inquiry' justice-affected people worked with one another, with researchers and with musicians to write songs that explored, represented and reflected on re/integration. (2) In 'Co-creative dialogue', some of the songs were shared and discussed through the production and release of an album and 2 EPs, a large range of public performances, a podcast series (The Art of Bridging), and other web-based materials. (3) In 'Co-creative discovery', a core group of the wider community of enquiry worked together to explore their learning and to assess what had been achieved in and through the project. Through these activities, Distant Voices aspired to develop theories and concepts of reintegration and rehabilitation, to influence related behaviours, to inform interventions and, more broadly, to encourage the development of a fairer and more vibrant society.